The impact of socio-scientific controversies in portuguese natural science teachers’ conceptions and practices - Reis, Pedro (2011)
This article discusses the results of a qualitative study, based on case studies, aimed at: (a) assessing a group of Portuguese secondary school natural science teachers regarding their conceptions of the nature, teaching and learning of science; (b) studying possible impacts of recent controversies surrounding scientific and technological issues on these conceptions and on teachers’ classroom practices. Five teachers, with different backgrounds and teaching experience, were observed during classes and interviewed with the purpose of studying: (a) the relationship between their conceptions and classroom practices; and (b) the factors that impede or enhance this relationship. Subsequently, observation notes and interview transcriptions were systematically analysed. The socio-scientific controversies recently discussed in Portugal seem to have had an impact on teachers’ (1) conceptions about the nature, teaching and learning of science; and (2) classroom practice. However, not all teachers were able to teach according to their conceptions. Some factors seem to mediate the relationship between teachers’ conceptions and classroom practice: National Curriculum, national exams, teachers’ previous experience as scientists, and personal educational priorities or aims. Based on the results obtained, some remarks and educational implications are discussed.